2023
DOI: 10.1002/jsfa.12647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar on rice yield, grain quality and starch viscosity attributes

Abstract: BACKGROUND Biochar can play a key role in improving paddy soil and productivity. However, there is limited information on the effects of biochar on rice quality and starch gelatinization. In this study, four rice straw biochar dosage treatments (0, 20, 40 and 60 g kg−1; CK, C20, C40 and C60, respectively) were set up to investigate rice yield components, rice processing, appearance and cooking quality, and starch gelatinization. RESULTS Addition of biochar increased the effective panicle, grain number per pani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This difference could probably be attributed to the differences between the distribution of starch granules, the content of amylose, and the proportion of amylose and amylopectin [ 51 ]. The BV represents the heat resistance of starch, and a lower BV within a specific range results in higher heat resistance [ 52 ]. In this study, N150+B significantly reduced the BV of starch, indicating that N150+B can increase its heat resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could probably be attributed to the differences between the distribution of starch granules, the content of amylose, and the proportion of amylose and amylopectin [ 51 ]. The BV represents the heat resistance of starch, and a lower BV within a specific range results in higher heat resistance [ 52 ]. In this study, N150+B significantly reduced the BV of starch, indicating that N150+B can increase its heat resistance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have investigated the potential impact of biochar application on rice grain quality. It has been suggested that biochar application can positively influence various grain quality traits, including milled rice rate, starch viscosity attributes, eating quality, and grain appearance, with the specific effects varying depending on the dosage of biochar used [184,186,187]. Furthermore, the combined application of biochar and a low nitrogen rate (135 kg/ha) has emerged as a promising approach for enhancing both yield and grain quality in a sustainable manner [184].…”
Section: Field Management Effects On Grain Qualitymentioning
confidence: 99%